2021
DOI: 10.1177/22925503211003838
|View full text |Cite
|
Sign up to set email alerts
|

Stack Splinting Versus Kirschner Wire Treatment in Acute Closed Mallet Finger Doyle I

Abstract: Introduction: Mallet injuries are common and usually treated conservatively. Various systematic reviews have found a lack of evidence regarding the best management, and it is still unclear. Objective: To evaluate the treatment efficacy of Stack Splinting compared to a Kirschner wire immobilization of acute closed mallet finger Doyle I. Methods: From March 2019 to February 2020, 41 patients with acute close mallet finger Doyle I were treated; 19 patients were treated with Kirschner wire and 22 with Stack splint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Closed tendonogenic mallet fingers are typically treated with splints or braces to immobilize the distal interphalangeal joint in hyperextension for 6 weeks, with generally positive outcomes. However, a study conducted by Velez 6 revealed that only seven out of 22 patients treated with splints completed the entire treatment process, and 15 of those experienced injury recurrence. The splint treatment failure rate for mallet fingers was as high as 68.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Closed tendonogenic mallet fingers are typically treated with splints or braces to immobilize the distal interphalangeal joint in hyperextension for 6 weeks, with generally positive outcomes. However, a study conducted by Velez 6 revealed that only seven out of 22 patients treated with splints completed the entire treatment process, and 15 of those experienced injury recurrence. The splint treatment failure rate for mallet fingers was as high as 68.2%.…”
Section: Discussionmentioning
confidence: 99%